Plastic-containing food waste conversion to biomethane, syngas, and biochar via anaerobic digestion and gasification: Focusing on reactor performance, microbial community analysis, and energy balance assessment. (15th March 2022) - Zhang, Le; Yao, Dingding; Tsui, To-Hung; Loh, Kai-Chee; Wang, Chi-Hwa; Dai, Yanjun; Tong, Yen Wah
Abstract: To manage the mixture of food waste and plastic waste, a hybrid biological and thermal system was investigated for converting plastic-containing food waste (PCFW) into renewable energy, focusing on performance evaluation, microbial community analysis, and energy balance assessment. The results showed that anaerobic digestion (AD) of food waste, polyethylene (PE)-containing food waste, polystyrene (PS)-containing food waste, and polypropylene (PP)-containing food waste generated a methane yield of 520.8, 395.6, 504.2, and 479.8 mL CH4 /gVS, respectively. CO2 gasification of all the plastic-containing digestate produced more syngas than pure digestate gasification. Syngas from PS-digestate reached the maximum yield of 20.78 mol/kg. During the digestate-derived-biochar-amended AD of PCFW, the methane yields in the biochars-amended digesters were 6–30% higher than those of the control digesters. Bioinformatic analysis of microbial communities confirmed the significant difference between control and biochar-amended digesters in terms of bacterial and methanogenic compositions. The enhanced methane yields in biochars-amended digesters could be partially ascribed to the selective enrichment of genus Methanosarcina, leading to an improved equilibrium between hydrogenotrophic and acetoclastic methanogenesis pathways. Moreover, energy balance assessment demonstrated that the hybrid biological and thermal conversion system can be a promising technical option for the treatment of PCFW and recovery of renewable biofuels (i.e., biogas and syngas) and bioresource (i.e., biochar) on an industrial scale. Graphical abstract: Image 1 Highlights: A hybrid bio/thermal system for plastic-containing food waste conversion to energy. Plastic/digestate gasification produced higher syngas yields than pure digestate. Gasification biochar enhanced methane yield by 6–30% in the AD processes. Biochar shifted methanogens toward a balance of two flexible methanogenic pathways. Average profit of PCFW treatment via the hybrid system is 20.7–64.2 US/ton waste.